Towards an updated reasoning formal theory - López-Astorga, Miguel (Aufklärung: journal of philosophy, 2016)
In the late twentieth century, the final version of the mental logic theory was presented. That was a syntactic and formal approach intended to describe and explain the human inferential ability. Maybe because of several experimental results achieved during the last years that have not addressed by the theory, it can be thought that its framework is outdated today. In this paper, I try to update some particular aspects of the mental logic theory by taking recent empirical evidence and arguments coming from the specialized literature into account. Such aspects refer to the symbols that it should adopt, its actual essential schemata, and the way in which the theory can deal with denials.